Antibiotic sensitivity of bacterias of the genus Listeria spp: isolated from bovine ground meat samples - Mantilla, Samira Pirola Santos (2008)
With the increasing use of antibiotics as growth promoters and even for therapeutical purposes on breeding of food-producing animals, there is the worldwide interest related to the ingestion of antibiotical residues on food and their effects on human health. The ingestion of food containing antibodies residues can cause bacterial resistence to the antibodies usually used on human therapies, what difficult the treatment of human infectious illnesses. Antibiotic sensitivity test was realized on Listeria spp. Strains, which were isolated from bovine meat samples, according to the National Committee for Clinical Laboratory Standards (NCCLS), 2003. According to the finding results, all isolated strains showed resistance to gentamicine, cefoxitine, ampicyline, clindamicine, oxacycline and sulfazotrim. L. innocua isolated strains showed resistance to gentamicine, cefoxitine, tetracycline, vancomicine, oxacycline and clindamicine.